2004
DOI: 10.1016/j.febslet.2004.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin membrane channels are mechanosensitive conduits for ATP

Abstract: Intercellular calcium wave propagation initiated by mechanical stress is a phenomenon found in nearly all cell types. The waves utilize two pathways: transfer of InsP3 directly from cell to cell through gap junction channels and release of ATP onto extracellular purinergic receptors. The conduit for ATP has remained elusive and both a vesicular and a channel mediated release have been considered. Here, we describe the properties of single pannexin 1 channels. They have a wide expression spectrum, they are of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
871
5
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 748 publications
(907 citation statements)
references
References 28 publications
27
871
5
4
Order By: Relevance
“…This raises the question of how ATP is released. Pannexin1 is expressed in human RBCs and has recently been suggested to operate as the ATP release channel in erythrocytes [12,28,29]. To assess the effect of pannexin 1 on ATP release, carbenoxolone and mefloquine were used as antagonists for pannexin 1 [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…This raises the question of how ATP is released. Pannexin1 is expressed in human RBCs and has recently been suggested to operate as the ATP release channel in erythrocytes [12,28,29]. To assess the effect of pannexin 1 on ATP release, carbenoxolone and mefloquine were used as antagonists for pannexin 1 [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…This model makes several other predictions that will be tested in the context of left-right patterning in the future, because the amount and distribution of serotonin, gap junctions, and ion transporters can be experimentally varied in this system. However, the analysis presented here can be used to model many other signaling systems in addition to serotonin; for example, other small molecules such as cAMP, ATP, and so on are known to pass through gap junctions (Cotrina et al, 1998(Cotrina et al, , 2000Braet et al, 2003;Bao et al, 2004) and have been suggested as candidate morphogens participating in the establishment of positional information (Schiffmann, 1989(Schiffmann, , 1991.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, invertebrate gap junctions are made of innexins, a family formerly called OPUS (Barnes, 1994). A variety of small molecules and metabolites are thought to permeate gap junctional paths, including cAMP (Burnside and Collas, 2002;Webb et al, 2002;Bedner et al, 2003), ATP (Bao et al, 2004;Pearson et al, 2005), and Ca ϩϩ (Toyofuku et al, 1998;Blomstrand et al, 1999;Paemeleire et al, 2000).…”
Section: Gap Junctional Signalingmentioning
confidence: 99%
“…Pannexins are structurally homologous to connexins and can form plasma membrane channels in Xenopus oocytes [93][94][95]. Several properties and findings make pannexin 1 a very attractive candidate for an ATP-releasing channel: (1) It can be activated by membrane depolarisation in the physiological range and allows permeation of small molecules including ATP [93][94][95]; (2) it can be activated at normal extracellular Ca 2+ concentrations [93]; (3) it is activated by mechanical perturbation [95]; (4) it may open under conditions of cellular energy depletion [96]; and (5) it can be activated by increase of intracellular Ca 2+ [95,97]. In addition, important evidence suggests that the longsought P2X 7 -related pore structure may be pannexin 1 [98,99].…”
Section: A Link To Connexins Pannexins and Atp-permeable Hemichannelsmentioning
confidence: 99%